EVALUASI MUTU DAN DAYA SIMPAN ROTI MANIS YANG DIBUAT MELALUI SUBSTITUSI TEPUNG TERIGU DENGAN MOCAF - Usman Pato; Evy Rossi; Rizqi Yanra; Dan Mukmin (Universitas Riau, 2011)
The demand of Indonesia for wheat flour is predicted to increase by at least 6% every year. Theobjective of this study was to find out the best formulation in production of sweet bread made from wheatflour substituted with Mocaf (Modified Cassava Flour). Each treatment of the research was conducted inthree replications. Parameters observed were contents of moisture, ash, and sucrose as well as leaveningpower, self life and organoleptic assessment of sweet bread. The data obtained were analyzed by ANOVAand was continued with DNMRT test at 5% level. Meanwhile the organoleptic data were analyzed byFriedman Test and data of gelatinous filament, flavor and rancidity were presented by descriptiveanalysis. Results showed that substitution of mocaf significantly influenced the levels of ash and sugar,leavening power and the organoleptic assessment of sweet bread. In general, substitution of 30% mocafhad met the Indonesian quality standard of sweet bread (SNI 01-3840-1995). In addition, the self life ofsweet bread in the treatment TM3 (wheat flour 70% and 30% mocaf) was similar to that of commercialsweet bread.Key words: sweet bread, mocaf, quality, substitution